Microsoft Windows scripting self-paced learning guide - Wilson, Ed, 1957- (Microsoft Press, 2004)
Get the inside track on how to write system administration scripts—straight from Microsoft scripting experts. This practical learning guide teaches how to use scripting techniques to gain control over your Microsoft Windows, Microsoft Internet Information Services (IIS), and Microsoft Exchange Server environments—all at your own pace. Build practical skills on everything from writing your first script in Microsoft Visual Basic® Scripting Edition (VBScript) to working with Windows Scripting Host (WSH), Windows Management Instrumentation (WMI), and Active Directory® Services Interface (ADSI), and from creating logon scripts to automating the management of systems, user accounts, files, printers, the registry, network services, directory services, security features, group policy, and more. The companion CD features the complete eBook, plus more than 200 sample scripts and a host of timesaving scripting tools.